A tecnologia móvel na aprendizagem colaborativa em uma comunidade de prática: para uma escola de seu tempo - Silva, Josefa dos Santos (Universidade Federal do Tocantins, 2018)
The research has the goal to know the pupils’ beliefs about the use of the mobile technologies, specifically the cellphone, and to identify practices of intervention which allow the insertion of the mobile technology into the school learning on a collaborative perspective, considering the prohibitive context for the use of cellphone to the Tocantinense schools. The bibliographic supply used is the sociocultural theory of Vygotsky (1978/1984) and Johnson (2009), the conception of Practice Community of Wenger (1998), Barbosa and Bedran (2016) Technology in the education with emphasis on interactivity and mobility Lévy (1996), Leffa (2005), Moraes (2004) and beliefs on Barcelos (2004).The methodology used is action-research, of ethnographic-oriented, on the perspective of a researcher-teacher for doing the intervention on the classroom, by using the cellphone resource and integrating it into the school learning process. The data generated have allowed us to indicate that the pupils’ beliefs related to the use of mobile set as while as learning resource are reformulated from the engagement and enterprise constituted in the Practice of Community of the classroom. The research result has pointed out that due the pupils make use of social networks on the posts in the communities which generally they serve to change a plenty of personal information, the act of using the applicative for the scientific knowledge, the movement of these pupils is to anchor at what they have already done and at what they have commonly posted into the other groups. Hence the reason of the teacher’s mediation, identified as the essential element on a sociocultural perspective of learning which contributes to the learner to overcome challenges and to make him/her motivated to construct other learning proposes by using his/her technological abilities as while as digital native, resigning, therefore, his/her beliefs in relation to the ICT ( Information and Communication Technologies) and his/her insertion into the learning.